The role of financing methods in the success of the management of small projects in the State of Kuwait - Kenemesh, Samira Abdel Wahab (Journal of Economic, Administrative and Legal Sciences, 2017)
This study aims to determine the role played by methods of funding small enterprises in the State of Kuwait towards the success of the projects through exploring the role of these methods, their specifications, the precautions pertaining to them, the role of financing institutions that provide the necessary funding for these projects and exploring the impact of these variables on the success of small enterprises in the State of Kuwait, Through descriptive analytical method to relevant literature in the field of finance, financing methods, small project funding methods and success factors. In light of analyzing previous literature, the study found a connection between methods of funding small enterprises in State of Kuwait and success of managing these projects, a relation between role of small project funding institutions in State of Kuwait and success of these projects on the other hand with the connection of specifications of finance methods, the safeguards and conditions of funding small enterprises with the success of such projects. Therefore, the study recommended linking the funding and its method in a manner consistent with duration of the project, establishing a specialized agency to implement the success factors of small enterprises, and work of finance institutions in Kuwait to diversify project financing methods.